Coping Strategies of Mothers in Raising Children with Autism: A Literature Review - Joan Beatrix; Rita Damayanti (Greenation Publisher & Yayasan Global Research National, 2024)
This study examines mothers coping strategies in raising children with autism through a literature review method. Mothers often encounter multifaceted challenges, including emotional, financial, and social difficulties, in caring for children with special needs. This study synthesizes existing research to identify effective coping mechanisms and the factors influencing their success. The literature review findings indicate that mothers predominantly utilize problem-focused and emotion-focused coping strategies. The effectiveness of these strategies is significantly influenced by variables such as social support, stress management, cognitive adaptation, participation in community or support groups, educational attainment, economic resources, and access to support services. These insights are crucial for practitioners and policymakers to develop interventions that better support mothers in managing the complexities of raising children with autism. The study also highlights the need for further research to determine the most effective interventions across diverse contexts.